2017
DOI: 10.1097/tp.0000000000001390
|View full text |Cite
|
Sign up to set email alerts
|

Proangiogenic Function of T Cells in Corneal Transplantation

Abstract: Background Corneal neovascularization increases the risk of T cell mediated allograft rejection. Here, we investigate whether T cells promote angiogenesis in transplantation. Methods Conventional effector T cells were collected from draining lymph nodes (DLNs) of allogeneic or syngeneic corneal transplanted BALB/c mice. T cells were either cocultured with vascular endothelial cells (VECs) to assess VEC proliferation or used in a Mixed Lymphocyte Reaction assay. mRNA expression of vascular endothelial growth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 53 publications
0
21
0
Order By: Relevance
“…Results shown are representative of three independent experiments. Samples sizes were estimated based on previous experimental studies on corneal transplantation 29,30,39,45,46 .…”
Section: Methodsmentioning
confidence: 99%
“…Results shown are representative of three independent experiments. Samples sizes were estimated based on previous experimental studies on corneal transplantation 29,30,39,45,46 .…”
Section: Methodsmentioning
confidence: 99%
“…e role of vascular endothelial growth factor in corneal neovascularization has been con rmed. e inhibitory e ect of vascular endothelial growth factor is currently being studied as a treatment for corneal neovascularization [30,31]. KEGG pathways in module 2 were mainly involved showed that Upregulated DEGs mainly participated in cell component (CC), while down regulated DEGs mainly took part in both cell component (CC) and molecular function (MF).…”
Section: Hub Gene Selectionmentioning
confidence: 99%
“…[13][14][15] In this model of ocular alloimmunity, approximately half of the grafts are rejected within 3 weeks of transplantation, while the remaining half survive indefinitely. [13][14][15] In this model of ocular alloimmunity, approximately half of the grafts are rejected within 3 weeks of transplantation, while the remaining half survive indefinitely.…”
Section: Introductionmentioning
confidence: 99%
“…We investigated the function of mast cells using a well-characterized murine model of corneal transplantation. [13][14][15] In this model of ocular alloimmunity, approximately half of the grafts are rejected within 3 weeks of transplantation, while the remaining half survive indefinitely. In comparison with other transplant models, this system permits the continuous evaluation of the alloimmune response (through the assessment of graft opacity) without necessitating host sacrifice.…”
Section: Introductionmentioning
confidence: 99%